2019
DOI: 10.1152/ajpcell.00308.2019
|View full text |Cite
|
Sign up to set email alerts
|

Statin administration activates system xC in skeletal muscle: a potential mechanism explaining statin-induced muscle pain

Abstract: Statins are a cholesterol-lowering drug class that significantly reduce cardiovascular disease risk. Despite their safety and effectiveness, musculoskeletal side-effects, particularly myalgia, are prominent and the most common reason for discontinuance. The cause of statin-induced myalgia is unknown, so defining the underlying mechanism(s) and potential therapeutic strategies is of clinical importance. Here we tested the hypothesis that statin administration activates skeletal muscle system xC−, a cystine/glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Importantly, we report here that increased myalgia trend with a significant increase in mitochondrial superoxide in PBMCs and platelets from statin users, while myalgia did not trend with other measures of mitochondrial respiration. This finding agrees with a recent study demonstrating a 41% increase in mitochondrial superoxide in mouse skeletal myotubes exposed to atorvastatin 50 . The study also demonstrated a statin-induced increase in glutamate efflux mediated by the xC - cysteine/glutamate antiporter, and argues that these factors could explain SAM 50 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Importantly, we report here that increased myalgia trend with a significant increase in mitochondrial superoxide in PBMCs and platelets from statin users, while myalgia did not trend with other measures of mitochondrial respiration. This finding agrees with a recent study demonstrating a 41% increase in mitochondrial superoxide in mouse skeletal myotubes exposed to atorvastatin 50 . The study also demonstrated a statin-induced increase in glutamate efflux mediated by the xC - cysteine/glutamate antiporter, and argues that these factors could explain SAM 50 .…”
Section: Discussionsupporting
confidence: 94%
“…This finding agrees with a recent study demonstrating a 41% increase in mitochondrial superoxide in mouse skeletal myotubes exposed to atorvastatin 50 . The study also demonstrated a statin-induced increase in glutamate efflux mediated by the xC - cysteine/glutamate antiporter, and argues that these factors could explain SAM 50 .…”
Section: Discussionsupporting
confidence: 94%
“…In addition, cystine levels and the sum of saturated/monounsaturated TGs were significantly altered in the S group. Cystine depletion in the S group can be explained by activation of the skeletal muscle system xC− (cystine/glutamate antiporter) induced by statin therapy, which causes myalgia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been increasing recognition of statin-associated myopathy, principally immune-mediated necrotizing myopathy (IMNM); however, it is still a relatively new entity and may not be initially considered in the differential for diffuse weakness [2,3]. The myalgia and myositis often associated with statin use have many proposed mechanisms including the inhibition of the production of CoQ 10, leading to mitochondrial dysfunction, increase in interstitial glutamate, sarcoplasmic reticulum calcium leak, and upregulation of genes involved in protein catabolism and the ubiquitinproteosome system [4][5][6][7]. While these adverse effects of statin use are unfortunate, they are often reversible upon discontinuation of the statin medication.…”
Section: Introductionmentioning
confidence: 99%